2013
DOI: 10.1364/oe.21.025685
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nonlinear noise in long, dispersion-uncompensated fiber links

Abstract: We study the properties of nonlinear interference noise (NLIN) in fiber-optic communications systems with large accumulated dispersion. Our focus is on settling the discrepancy between the results of the Gaussian noise (GN) model (according to which NLIN is additive Gaussian) and a recently published time-domain analysis, which attributes drastically different properties to the NLIN. Upon reviewing the two approaches we identify several unjustified assumptions that are key in the derivation of the GN model, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
375
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(396 citation statements)
references
References 14 publications
17
375
0
4
Order By: Relevance
“…8 the ACF of the estimated PN is given for several L. The theoretical ACF as calculated in [1] is also given. The ACF of the TMM algorithm is calculated by first estimating the valuesθ k = arg max p(θ k |y K 1 ), and then calculating the ACF of the processΘ.…”
Section: Nonlinear Phase Noise Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…8 the ACF of the estimated PN is given for several L. The theoretical ACF as calculated in [1] is also given. The ACF of the TMM algorithm is calculated by first estimating the valuesθ k = arg max p(θ k |y K 1 ), and then calculating the ACF of the processΘ.…”
Section: Nonlinear Phase Noise Propertiesmentioning
confidence: 99%
“…It has been previously shown that the NLIN is not completely random [1] and its properties can be used for partial mitigation. Particularly, the phase and polarization rotation noise (PPRN) part of the NLIN exhibits long temporal and spectral correlations [2], which can be exploited for its compensation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The input constellation in this case is 256QAM and the input power is −4dBm, which we found to be optimal at this distance. As shown in [2] [22], the NLPN is highly correlated within a window of several tens of symbols, which can be exploited in order to estimate the actual phase noise samples asθ where L + 1 is the window size, (·) * denotes complex conjugate, and (·) denotes the angle of a complex number. We then compare the estimated PSD of {θ k } to the theoretical PSD of a Wiener process given by the Lorentzian function with process noise variance…”
Section: B the Non-linear Termmentioning
confidence: 99%
“…A model is also proposed that allows to calculate the auto correlation function (ACF) of the phase noise. Using the time domain ACF properties, the authors in [2] separate the contribution of the noise into linear and non-linear part, and thereby are able to show potential increase in the maximum achievable rate in a point to point WDM link. A strategy for canceling the phase noise is proposed in [5], based on a frequency domain equalizer.…”
mentioning
confidence: 99%
See 1 more Smart Citation